Pengaruh Tingkat Kesadaran Terhadap Kepatuhan Masyarakat Dalam Membayar Zakat Mal - Andi Suhandi; Azmy MH; Bayu Umara; Bernad Hananto; M Ulil Albab (LPPM STEBIS YPII, 2024)
This study aims to determine the Level of Awareness of Community Compliance in Paying Mal Zakat. This research was conducted in Cibatu Village, examining how the influence of the community in paying zakat mal and finding out the potential of zakat in Cibatu Village. In this study, using a type of field research (field research) with a quantitative approach through distributing questionnaires and questionnaires that have been distributed directly to the informants. Research on the level of awareness of community compliance in paying zakat mal. The population that will be the object of research is as many as 100 sources. Based on the results of research data analysis and calculations that have been carried out by researchers, it can be concluded that there is a significant influence between the level of awareness of public compliance in paying zakat mal. With a coefficient value of 0.867 when compared with the value of rtable at a significant level of 5% of 0.195, then rcount > rtable (0.867> 0.195) so that the coefficient value is significant. The results of the analysis conducted by researchers obtained the value of fcount of 296.416. When compared with the value of the fable with a significance level of 5% of 3.09. Then fcount > ftable (296,416> 3.09) so that this value can be said to be significant. This means that the level of awareness of compliance has a simultaneous effect on the community in paying zakat mal.